Blessed - Smith, Cynthia Leitich (Smith, Cynthia Leitich. Tantalize series, 2011)
Even as teenaged Quincie Morris adjusts to her appetites as a neophyte vampire, she must clear her true love, the hybrid-werewolf Kieren, of murder charges; thwart the apocalyptic ambitions of Bradley Sanguini, the vampire-chef who "blessed" her; and keep her dead parents' restaurant up and running before she loses her own soul.